FAMOUS ENLIGHTENED WRITER AND DRAMATURGER-ABDULLA AVLONI (Archive of Conferences, 2021)
One of the great representatives of Uzbek literature is Abdullah Avloni it is literally the duty of every young generation. Indeed, the leader in his works The study and research of pedagogical views and ideas is not only the passion of the teaching process and perhaps improve the quality of education. Throughout this article, we Try to get acquainted with the main ideas of Abdullah Avloni's works we do